Injection of oxygen vacancies in the bulk lattice of layered cathodes - Yan, Pengfei; Zheng, Jianming; Tang, Zhen-Kun; Devaraj, Arun; Chen, Guoying; Amine, Khalil; Zhang, Ji-Guang; Liu, Li-Min; Wang, Chongmin (Nature nanotechnology, 2019)
Surfaces, interfaces and grain boundaries are classically known to be sinks of defects generated within the bulk lattice. Here, we report an inverse case by which the defects generated at the particle surface are continuously pumped into the bulk lattice. We show that, during operation of a rechargeable battery, oxygen vacancies produced at the surfaces of lithium-rich layered cathode particles migrate towards the inside lattice. This process is associated with a high cutoff voltage at which an anionic redox process is activated. First-principle calculations reveal that triggering of this redox process leads to a sharp decrease of both the formation energy of oxygen vacancies and the migration barrier of oxidized oxide ions, therefore enabling the migration of oxygen vacancies into the bulk lattice of the cathode. This work unveils a coupled redox dynamic that needs to be taken into account when designing high-capacity layered cathode materials for high-voltage lithium-ion batteries. Lithium transition metal oxide cathodes can degrade under high-voltage conditions by a redox mechanism by which oxygen vacancies form at the surface and migrate towards the bulk.